Click Reaction Inspired Enzyme Inhibitors in Diabetes Care: An Update in the Field of Chronic Metabolic Disorder - Mudgal, Deeksha; Yadav, Nisha; Srivastava, Gaurav Kumar; Mishra, Manish; Mishra, Vivek (Current Pharmaceutical Design, 2025)
Diabetes is a chronic metabolic disorder that impacts all age groups and affects a large population worldwide. Humans receive glucose from almost every food source, and after absorption from the gut, it reaches the liver, which functions as the distribution center for it. The insulin-responsive glucose transporter type 4 (GLUT-4) is a major carrier of glucose to the various cells (majorly expressed in myocytes, adipocytes, and cardiomyocytes) in a well-fed state. In fasting periods, the glucose supply is maintained by glycogenolysis and gluconeogenesis. In diabetes, the distribution of glucose is hampered due to several reasons. Furthermore, to treat this disorder, several drugs have been synthesized, and click chemistry plays an important role. A more recent concept for producing pharmaceuticals with a click chemistry approach makes any reaction more practical and stereospecific, along with a higher yield of products and a smaller number of by-products. This approach comprises a compiled study of the activity of numerous compelling antidiabetic drugs containing 1,2,3-triazole derivatives supported by click chemistry. In this review, we discuss the synthetic antidiabetic drugs made via click chemistry and their commendable role in improving diabetes care.
Keywords: inhibitors